Is it time we better understood the tests we are using for return to sport decision making following ACL reconstruction? A critical review of the hop tests - Davies, W. T.; Myer, G. D.; Read, P. J. (Sports Medicine, 2020)
There has been a move towards a criterion-based return to play in recent years, with 4 single-leg hop tests commonly used to assess functional performance. Despite their widespread integration, research indicates that relationships between `passing` `hop test criteria and successful outcomes following rehabilitation are equivocal, and, therefore, require further investigation. This critical review includes key information to examine the evolution of these tests, their reliability, relationships with other constructs, and sensitivity to change over time. Recommendations for how measurement and administration of the tests can be improved are also discussed. The evidence presented in this review shows that hop tests display good reliability and are sensitive to change over time. However, the use of more than 2 hop tests does not appear to be necessary due to high collinearity and no greater sensitivity to detect abnormality. The inclusion of other hop tests in different planes may give greater information about the current function of the knee, particularly when measured over time using both relative and absolute measures of performance. It is recommended that the contralateral limb be tested prior to surgery for a more relevant benchmark for performance, and clinicians are strongly advised to measure movement quality, as hop distance alone appears to overestimate the recovery of the knee.